2022
DOI: 10.3389/fcell.2022.816153
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Multi-Omics Alteration, Immune Profile, and Pharmacological Landscape of Pyroptosis-Derived lncRNA Pairs in Gastric Cancer

Abstract: Background: Recent evidence demonstrates that pyroptosis-derived long non-coding RNAs (lncRNAs) have profound impacts on the initiation, progression, and microenvironment of tumors. However, the roles of pyroptosis-derived lncRNAs (PDLs) in gastric cancer (GC) remain elusive.Methods: We comprehensively analyzed the multi-omics data of 839 GC patients from three independent cohorts. The previous gene set enrichment analysis embedding algorithm was utilized to identify PDLs. A gene pair pipeline was developed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Figures 9A,B show that there were no significant differences between age groups (≤65 and >65 years old) and gender. A previous study reported that the collagen proportional area (CPA) measurement may be a useful prognostic indicator for HCC ( Guo et al, 2022 ). Our study demonstrated that there were statistically significant differences among all CPA stages ( Figure 9C , C1: 0%–5%, C2: 5%–10%, C3: 10%–20%, C4: >20%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figures 9A,B show that there were no significant differences between age groups (≤65 and >65 years old) and gender. A previous study reported that the collagen proportional area (CPA) measurement may be a useful prognostic indicator for HCC ( Guo et al, 2022 ). Our study demonstrated that there were statistically significant differences among all CPA stages ( Figure 9C , C1: 0%–5%, C2: 5%–10%, C3: 10%–20%, C4: >20%).…”
Section: Resultsmentioning
confidence: 99%
“…To determine the proportions and differences in immune cells in different risk groups, we used ssGSEA in the R package GSVA to evaluate the infiltration level of 28 types of immune cells. The detailed method has been described in previous studies ( Liu et al, 2021 ; Guo et al, 2022 ). The Wilcoxon test was used to compare the differences between the high- and low-risk groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune cell bubble plots showed that low-risk groups had higher levels of immune infiltration. It has been reported that the high immune infiltration state tends to have a better immunotherapeutic effect ( Guo et al, 2022 ; Luo et al, 2022 ). Interestingly, immune scores and immune checkpoint expression levels were also higher in the low-risk group, which is consistent with the results of Yu et al (2021) .…”
Section: Discussionmentioning
confidence: 99%
“…KM and ROC curves indicate that NLPS can accurately predict the prognosis of patients in different centers, which suggests that NLPS has clinical generalizability. Prognostic differences between patients were often due to their underlying molecular mechanisms and characteristics ( Guo et al, 2022 ). Based on the GSEA and GSVA algorithms, we further explore the biological characteristics of patients in the high- and low-risk groups.…”
Section: Discussionmentioning
confidence: 99%